STUDI EVALUASI TERHADAP KEBIJAKAN PENGELOLAAN HUTAN BERSAMA MASYARAKAT (PHBM) DI KABUPATEN PEMALANG TAHUN 2012-2014 - MAHARANI DIAN PUSPITA; SUSILO UTOMO; SULISTYOWATI . (Journal of Politic and Government Studies, 2016)
This research is made to explain the result of evaluation study on Collaborative Forest Management (CBFM) in Pemalang Regency in the years 2012-2014. The purposes of this policy are (1) increase prosperity, quality of life, economic capacity, and society’s social, (2) increase the role and responsibility of PT Perhutani (Persero), society of forest village, and the interested parties to forest resource management, (3) increase quality of forest resource, productivity, and forest’s security, (4) encourage and harmonize forest resource management that appropriate with regional development activity, also suitable with social dynamic condition of forest village society, and (5) create employment, increase chance of have a business, and also increase both society and state income.To explain the evaluation of implementation and the result of Collaborative Forest Management (CBFM) this research used qualitative method which focused on purposive sampling technique and snowball sampling method. The data was obtained from primary and secondary data. The methods of collecting data used were interview, documentation, and literature study.The result showed that the implementation of Collaborative Forest Management (CBFM) in Surajaya Village, Pemalang Regency, in the years 2012-2014 has worked well. The aim of this policy has achieved that proved by the high participation of farmer following PHBM’s activity, the security of forest is decrease, and maintaned ability of farmer to forest resource management. The policy has given benefit to target, for example economic needs’s farmer can be fulfilled in daily life, society can utilize land freely, capability to increase prosperity and absorption of labor. In the other hand, the implementation of this policy has obstacle in its target and the implementation. However, the government, executor institute or Perhutani, and target want to this policy to be still defended. The expectation is this policy still be continued and improved, for example in funding for PHBM activity.Keyword: policy evaluation, Collaborative Forest Management, forest conservation and empowerment